Optimal Modeling of Load Variations in Distribution System Reconfiguration - Mahdavi, Meisam [UNESP]; Javadi, Mohammad S.; Wang, Fei; Catalão, João P.S. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Distribution networks have a prominent role in electricity delivery to individual consumers. Nevertheless, their energy losses are higher than transmission systems, which this issue affects the distribution operational costs. Hence, the minimization of power losses in distribution networks has particular importance for the system operators. Distribution network reconfiguration (DNR) is an effective way to reduce energy losses. However, some research works regarding DNR have not considered load variations in power loss calculations. Load level has an essential role in network losses determination and significantly influences the energy losses amount. On the other hand, considering load variations in DNR increases the computational burden and processing time of the relevant algorithms. Therefore, this paper presents an effective reconfiguration framework for minimization of distribution losses, while the energy demand is changing. The simulation results show the effectiveness of the proposed strategy for optimal reconfiguration of distribution systems in presence of load variations.
Keywords: demand variations; Distribution systems; DNR; efficient reconfiguration strategy; energy losses